A review of e-service quality dimensions in user satisfaction - Al-Nuaimi, I.T.I. (2013)
Quality of e-service is one of the significant factors that play a major role in the success or failure of online organizations. It enhances the competitive advantages of online organization; in addition, it improves the relationships with clients and increases their satisfactions. Measuring online service quality becomes industry or context dependent in which, it may increase the difficulties to constitute a global measure. This paper reviews e-service quality literature in Malaysian educational institutions because it is of great importance in attracting and retaining tuition-based returns for education in Malaysia, which has become an increasingly competitive business. Â© 2013 IEEE.